Enhancing value cocreation orientation in service innovation: a new service development and service design integrated process - Henrique Lermen, Fernando (2025)
Integrating the prescriptive and linear approach of NSD with the non-linear approach of service design can enhance value cocreation orientation in service innovation. Then, the objectives of this study are to explore these complementarities, propose an integrated model that enhances value cocreation in service innovation, and evaluate this model. The methodology involved a systematic literature review, focus group, and brainstorming session to propose the model, followed by evaluation through three case studies and expert interviews. As results, the model’s main feature is the development of each service prerequisite through the service design cycle, prescriptively incorporating customer input throughout the service innovation process. Expert interviews and model application indicated that the model achieved its objectives, as the development of each service element was based on a deep understanding of customer demands and their active participation, resulting in services with high potential for resource integration and value cocreation. After applying and evaluating the model, this study provides evidence that (i) hybrid waterfall-cyclic dynamic contributes to managing complexity in service innovation, while maintaining customer focus and creativity; (ii) recurring studies of customer needs in distinct service innovation phases, each focusing on a specific service element, contribute to enriching the understanding of such needs; (iii) active customer involvement in proposing and selecting each service prerequisites across service innovation phases tends to enhance resource integration and value cocreation; (iv) waterfall and cyclic hybrid approach for service innovation contributes to generating detailed service prerequisites specifications, leading to more effective implementation; and (v) customer-centered dynamics throughout the service innovation process contribute to promoting cross-departmental integration, embedding customer needs across the organization. This paper contributes to deepening the discussion on implementing value cocreation in service innovation.